Crop residues and feed management - International Livestock Research Institute (ILRI, 2023)
In parts of Ethiopia, crop residues are the main sources of roughage as feed for livestock. This video is a short guide to how farmers in Ethiopia can improve the palatability and nutrition of crop residues, make affordable concentrate feed, use EM 1 and in haymaking. The information in this video is a collection of knowledge from farmers, and extension officers. It was put together by ILRI partners in the AfricaRising and the Program for Climate Smart Livestock (PCSL) project and is being disseminated and used by the Livestock and Climate Initiative.